Destination images of the ten most visited countries for potential Brazilian tourists - Jean Max Tavares; Xuan Tran; Lori Pennington-Gray (Tourism & Management Studies)
The principal aim of this study was to verify which destination images of the ten most visited countries in the world in 2014 were rated by Brazilians who have never been to another country. A survey was applied to 263 respondents with the following variables: safety, the price of accommodation, the cost of transport, the duration of the trip, the economic stability of the destination, the political and social stability, the singular tourist attractions, the weather, the local infrastructure, and the friendliness of the local community. Using Partial Least Squares Path Modelling and ANOVA, six hypotheses were tested. The results obtained showed that those countries which are the nearest to Brazil were better evaluated (except for England and France). Safety, followed by the price of accommodation, and the cost of transportation, were the most important attributes of the images in the countries that were best evaluated by potential Brazilian tourists.